Pendampingan Tadarus Juz Amma, Pembacaan Asmaul Husna, dan Bacaan Sholat dalam Membentuk Kedisiplinan Beribadah Siswa - Titania Amilia Putri; Sri Hidayati; Helnawaty Helnawaty (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Religious education plays a very important role in shaping the discipline and moral character of students, especially at the primary level. This community service aims to assist students of class VI A at MI Darul Ulum Palangka Raya in tadarus Juz Amma, reciting Asmaul Husna, and reciting the obligatory prayers, as an effort to improve the discipline of worship. This activity uses the ABCD (Asset-Based Community Development) method, which utilises school assets and the potential of students and teachers. MBKM Teaching Assistance programme students play an active role in collaboration with the VI A class teacher to accompany students during the activity. The results of this assistance show significant improvement in students, especially in the ability to read the Qur'an with tartil and correct tajweed, memorise Asmaul Husna, and recite prayer readings correctly. This activity, which is routinely carried out every morning, not only improves the understanding of worship techniques, but also familiarises students to carry out worship consistently. This assistance fosters students' sense of responsibility and discipline in carrying out worship obligations.